Flour blending can mitigate food insecurity and economic stress - Poole, Nigel D.; Donovan, Jason A.; Kariuki, Sarah K.; Rutsaert, Pieter; Ibba, Maria Itria; Bentley, Alison R. (Elsevier, 2024)
Cereal flour blending can reduce food insecurity risks, as well as contribute to economic and nutrition goals. Yet, the potential for blending has not been realized, and new products have not become scalable commercial propositions. Numerous experiments have shown the potential to produce acceptable foods derived from blended flours of diverse crops including wheat. An important question is whether the incentives, capacities and needs of farmers, processors and consumers have been considered. We argue that technical solutions must be developed within a specific agroecological, commercial, economic, and political environment. Innovations must address the clearly defined objectives of a wheat flour blending policy, if the potential benefits of blending for addressing food insecurity and economic stress are to be achieved.